An Autopsy-Based Correlation Study About Determination of Sex from the Width of S1 Segment of Sternum in the Central India Indore Region (M.P.) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Determination of sex from the skeletal remains is of immense importance in the field of forensic medicine, physical anthropometry and anthropology. Various previous studies have demonstrated sternum as an important tool for the determination of sex. Sternum bone is very important bone for age and sex determination in the mutilated, fragmented bodies and in advance stage of decomposition. Exact determination of sex from skeleton has been a critical issue in medico-legal cases and the accuracy depends on the type of material available and methods applied. Sternum is a bone which is easily retrievable even from the advance decomposed body and also from the bundle of bone so it become a very important bone. Total 632 subjects, with 350 male and 282 female of the age >25 years, were taken in our study and data analysis was done using SPSS software and relevant statistical test was applied. In our study, bisexual variation in relation to width of S1 segment of mesosternum was found conclusive.
Keywords: Anthropometry; Bisexual variation; Decomposed body; Medicolegal case; Sex determination; Width of S1 segment